3527 Quantifying the psychosocial benefits of masculinizing chest reconstruction in transgender men with patient reported outcomes: The GENDER-Q. (27th March 2019) - Kennedy, Adrienne; Alcon, Andre; Kim, Esther
Abstract : OBJECTIVES/SPECIFIC AIMS: 1. To evaluate the effects of masculinizing chest reconstruction on the quality of life of female-to-male transgender individuals. 2. To develop and validate a quality of life survey for female-to-male transgender individuals undergoing masculinizing chest reconstruction gender-affirming surgery. METHODS/STUDY POPULATION:. We developed and refined the GENDER-Q using focus groups and exploratory interviews with FTM individuals that were recorded, transcribed, and coded. All consenting FTM patients undergoing chest reconstruction at UCSF Parnassus Medical center between 2017-2019 who meet World Professional Association for Transgender Health (WPATH) criteria for gender dysphoria will be enrolled in the study. The GENDER-Q will be co-administered with the WHO Quality of Life-BREF survey pre-operatively, 6 weeks post-operatively, and one year post-operatively through REDCAP, an online survey database. RESULTS/ANTICIPATED RESULTS: Approximately 70 patients will be enrolled in the study. Preliminary results detect statistically significant mean quality of life post-operative improvements in all three sections (Physical Health, Gender Presentation, Psychological Health) of the GENDER-Q at 6-week follow up that is maintained at one-year (p< 0.005). Statistically significant improvements were similarly achieved and maintained with the WHO QOL-BREF survey (p< 0.05). The mean reported improvement from baseline to follow-up appears to be more pronounced in the GENDER-Q survey compared to WHO QOL-BREF. The median time to complete the pre and post-operative surveys was 10 minutes. Calculation of Cronbach's (0.67-0.81) and the Pearson Correlation Coefficient for each section revealed excellent internal validity. DISCUSSION/SIGNIFICANCE OF IMPACT: There are few studies assessing quality of life outcomes in transgender patients undergoing gender-affirming surgeries. A standardized and validated assessment tool will provide the means for which data can be pooled in large multi-center studies. Providing further evidence to support the positive health outcomes of gender-affirming surgeries can lead to broader access and reduce healthcare disparities among transgender populations.